ANALYSIS OF THE PROSPECTS OF THE IMPLEMENTATION OF HYDROGEN ENERGY IN THE ENERGY BALANCE OF COMPANIES IN THE AVIATION INDUSTRY - BOYKO, Serhiy; KOTOV, Oleksiy; VYSHNEVSKY, Svyatoslav; MELNYK, Olga; PODHORNYH, Nadia (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Hydrogen energy technologies, such as hydrogen storage of energy from renewable sources of electricity, by storing hydrogen as a battery for autonomous and distributed generation and refueling for hydrogen transport, are actively being introduced into the transport industry of developed countries. The transport industry of Ukraine is inextricably linked with the energy industry and has its own characteristics. World experience shows that the introduction of the latest technologies in the transport sector definitely gives a number of unambiguous bonuses for further stable development. Meanwhile, the objects of the transport industry of Ukraine have significant territories that are technologically not involved in the agricultural industry and cannot be used for the development of the cultural and social sphere. In turn, the objects of the transport industry of Ukraine make up its transport infrastructure and are located throughout the territory of Ukraine. Today, hydrogen energy includes a set of technologies for production, transportation, accumulation and use of the universal secondary energy carrier – hydrogen. Thus, in the concept of hydrogen energy, hydrogen complements the most important secondary energy carrier – electricity, the energy use of hydrogen is determined by the possibility of environmentally clean production of electricity and long-term storage with the minimization of losses, including in large volumes. The development of renewable energy, which receives energy from variable natural resources of solar and wind energy, as well as the active implementation of technologies of distributed generation and “smart” networks stimulate the urgency of solving the problem of long-term energy storage. The approach is also designed to settle the issue of the use of wind turbines and SPPs in power supply systems by stabilizing the return of the electric energy generated by them to the network. Undoubtedly, WPPs and SPPs can be connected to the network if necessary, meanwhile, using the proposed approach there is an opportunity to reduce the loss of energy obtained from natural sources and to use it rationally and efficiently. In the conditions of aviation industry enterprises, it is relevant and possible to introduce into the general structure of power supply systems based on renewable energy sources. The proposed approach to the introduction of hydrogen energy in the conditions of aviation industry enterprises allows to effectively use sources of electrical energy based on renewable energy sources both in autonomous power supply systems and to integrate them into existing power supply systems